A Modelling of Tunnelling Current through a Trapezoidal Potential Barrier by Using Exponential Wavefunction Approach - Fitriyadi - (Institut Teknologi Bandung, 2021)
A tunnelling current through a trapezoidal barrier potential has been modelled. The transmittance is determined using the exponential wavefunction approach method. Furthermore, the transmittance is used to calculate the tunnelling current density by applying the Gauss-Laguerre quadrature method. The simulation results show the increasing bias voltage causes the raising tunnelling current, and an increase of temperature is proportional to the tunnelling current.